2022
DOI: 10.46234/ccdcw2022.206
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Monkeypox Virus from the First Case of Monkeypox — Chongqing Municipality, China, 2022

Abstract: Introduction: The first imported case of monkeypox (MPX) from the mainland of China was reported in September 2022. Herein, the study reports the isolation and characterization of MPX virus (MPXV) in this case.Methods: Clinical specimens including skin blister fluid, oropharyngeal and nasopharyngeal swabs, and blood were collected and inoculated onto Vero cells. The isolated virus was identified as MPXV using quantitative polymerase chain reaction (qPCR), cytopathic effects (CPEs), immunofluorescence assay (IF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 12 publications
1
54
0
Order By: Relevance
“…China has implemented strict entry screening measures, and screening for COVID-19 during the quarantine period is accompanied by Mpox testing [ 34 ]. Therefore, apart from two imported cases of Mpox in Hong Kong and Chongqing, there are currently no autochthonous cases of Mpox that have been reported in China, so there is no widespread concern [ 35 , 36 ]. Social restrictions have varied from province to province.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…China has implemented strict entry screening measures, and screening for COVID-19 during the quarantine period is accompanied by Mpox testing [ 34 ]. Therefore, apart from two imported cases of Mpox in Hong Kong and Chongqing, there are currently no autochthonous cases of Mpox that have been reported in China, so there is no widespread concern [ 35 , 36 ]. Social restrictions have varied from province to province.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, participants’ perceptions of the Mpox threat and willingness to get the Mpox vaccine may change as the situation evolves. It is worth noting that there were no Mpox cases reported in mainland China at the time of data collection, until the first imported case was reported in Chongqing, China on 16 September 2022 [ 36 ]. Future studies could explore the impact of this factor on Mpox perception in this population.…”
Section: Discussionmentioning
confidence: 99%
“…This pipeline is designed for the Oxford/Nanopore sequencing platform and can easily assemble and analyze mutations in the MPXV genome. Based on our experience with sequencing the genome of the first imported case of mpox in Chinese mainland, we have developed a bioinformatics pipeline that is suitable for analyzing amplicon sequencing data obtained from both next- and third-generation sequencing platforms ( Zhao et al 2022 ). The pipeline can be found at https://github.com/BioWu/Monkeypox-genome-assembly .…”
Section: Discussionmentioning
confidence: 99%
“…As of March 5, 2023, 86,309 confirmed mpox cases have been reported from 107 countries (regions) worldwide ( Who, 2023 ). In the mainland of China, the first imported case was confirmed by the Chinese Center for Disease Control and Prevention ( Zhao et al 2022 ), making this the fifth confirmed mpox infection in China. Neglected zoonotic mpox has been restricted in Africa but now it is back in the spotlight worldwide (Tan et al 2022).…”
mentioning
confidence: 95%
“…The Polymerase Chain Reaction (PCR) is a normally preferred method for the diagnosis of mpox due to its high accuracy and sensitivity. [13] The lesion sample is stored cold in a dry sterilized tube for diagnosis. In the case of PCR blood tests, PCR-based diagnosis is generally inconclusive because the duration of viremia is shorter than when the sample was collected after the onset of symptoms and should not be collected regularly from the patient.…”
Section: Diagnosismentioning
confidence: 99%